Using Photovoltaic Panels for Irrigation - Senpinar, A. (Polish Acad Sciences Inst Physics, 2017)
Renewable energy sources are getting more and more popular due to the increasing world population and decreasing conventional sources. In recent years, climate change and global warming have also increased the amount of water needed for irrigation. Renewable energy sources may therefore be used to develop photovoltaic pumping systems. Using photovoltaic arrays to drive water pumping units for irrigation in remote areas and desert regions is an economical solution. The sizing of photovoltaic pumping systems is important in order to optimize the power peak of photovoltaic array and for the choice of motor, pump and inverter (when needed). A photovoltaic pumping system consists of at least six basic components: a photovoltaic array, a dc pump motor, a battery-charge regulator, a water tank, humidity sensors and an electronic control unit. The usage of such system is in a natural relationship between the availability of solar radiation and water requirement. In this study, the designed system is an electronically controlled system, based on humidity sensors. The water requirement increases with increasing solar radiation. Hence, the dc motor is operated by means of an electronic control unit. When humidity in the soil reaches a certain value, the dc motor is stopped. The operation of the control unit relies on the data received from humidity sensors. The designed system was implemented and the obtained results were satisfactory.
3rd International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 19-24, 2016 -- Antalya, TURKEY
Keywords: Solar-Radiation; Pumping Systems; Simulation; Model